Effect of dietary L-carnitine on growth, carcass characteristics, and metabolism of swine - Owen, K.Q.; Ji, H.; Maxwell, C.V.; Tremblay, G.C.; Koo, S.I.; Blum, S.A.; Nelssen, Jim L.; Goodband, Robert D.; Tokach, Michael D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Thirty six Yorkshire gilts (initially 123 lb BW) were used to investigate the effect of dietary carnitine on growth performance, carcass characteristics, fatty acid oxidation, and enzyme kinetics. Dietary carnitine reduced fat deposition in favor of protein deposition, stimulated fatty acid oxidation, induced the expression of pyruvate carboxylase, increased the capacity of pyruvate carboxylase flux, and decreased the capacity of branch chain keto dehydrogenase.
Keywords: Swine; Carnitine; Feed efficiency; Carcass